THE INTERPRETATION OF INTERNATIONAL AGREEMENTS BY THE COURT OF JUSTICE OF THE EUROPEAN UNION - Roxana-Mariana POPESCU (Challenges of the Knowledge Society)
According to a settled case-law, the Court held that the agreements, to which the Union is party, mixed or not, should be treated as legal acts adopted by EU institutions, in order to be introduced in the scope of art. 267 section a) TFEU1. In the study below, we shall present jurisprudential issues concerning the competence of the Court in Luxembourg on the interpretation of international agreements by the Court of Justice of the European Union.